Upaya Guru dalam Mengoptimalkan Berbagai Tingkat Pemahaman Peserta Didik - Rizky, Retno; Hannan Nur Rizki Sawaludin; Rina Fatmawati (CV. Aksara Global, 2025)
Abstract. In an effort to optimize the understanding of teachers' role learners is essential, such as the use of various learning strategies and methods, effective interactions between teachers and learners are expected to improve the quality of learning and develop the potential of learners. The study uses a descriptive qualitative approach. Descriptive language is used to describe phenomena in detail and accuracy. The purpose of this study is to look at the strategies teachers use, the management of the class includes evaluation and measurement, and the challenges teachers face in efforts to optimize the understanding of learners. The data-gathering technique in this study is an interview. The type of observations used are non-participative observations so that researchers are not involved in the learning process in the classroom. Research shows that in an effort to optimize the various levels of understanding teachers learners implement strategies and good class management. This was shown with the results of the interview with the 4.3 grade teacher.Keywords: Educational comprehension, teacher effort, optimizing